Complement activation and HLA-B27. Issue 3 (March 1988) - Meri, S; Partanen, J; Leirisalo-Repo, M; Repo, H
Abstract : The efficiency of complement activation was studied in sera from HLA-B27 positive and negative subjects (27 with previous yersinia arthritis and 35 controls). Activation of complement with zymosan induced higher mean levels of the anaphylatoxin C3a in HLA-B27 positive sera (mean (SD) 7.40 (1.66) mg/l) than in HLA-B27 negative sera (6.41 (1.79) mg/l). Similarly, higher levels of C3d, g, another C3 breakdown fragment, were obtained in HLA-B27 positive sera after Escherichia coli 0111:B4 lipopolysaccharide treatment (17.6 (3.7)% v 15.0 (3.8)%). The differences occurred irrespective of previous arthritis, complement C4 or Bf phenotype, or variation in background complement levels. The findings suggest that an increased responsiveness to complement activators may contribute to the pathogenesis of HLA-B27 associated inflammatory diseases.